Advanced Foreign Experiences In Training Service Dogs And Their Significance - Associate Professor, Colonel Karimjonova Munavvar Ibragimovna (Genius Journals, 2025)
This article analyzes and examines the training of service dogs in the field of cynology in law enforcement agencies of the Republic of Uzbekistan, as well as advanced world experience. It also highlights scientific proposals and practical recommendations in the field of cynology
Keywords: Service dog; behavior; special training